2008
DOI: 10.1002/app.27746
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐induced enhancement of the dissolution rate of poorly water‐soluble tibolone from poly(ethylene glycol) solid dispersions

Abstract: In this study, solid dispersions of poorly water-soluble Tibolone in a poly(ethylene glycol) matrix were prepared with conventional melt mixing and microwave irradiation. The results of the assay content, LC-MS, and 1 H-NMR indicated that microwave irradiation did not affect drug stability when a relatively low irradiation power (440 W) was used. Fourier transform infrared spectroscopy indicated that there were no hydrogen bonds formed between Tibolone and poly(ethylene glycol), and this affected the drug's cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…In a recent study, Papadimitriou et al [67] used microwave irradiation in place of conventional heating to melt the drug and carrier mixtures. The resulting dispersion was compared with samples prepared by the conventional fusion technique.…”
Section: Solid Dispersionsmentioning
confidence: 99%
“…In a recent study, Papadimitriou et al [67] used microwave irradiation in place of conventional heating to melt the drug and carrier mixtures. The resulting dispersion was compared with samples prepared by the conventional fusion technique.…”
Section: Solid Dispersionsmentioning
confidence: 99%
“…In fact, compared with conventional heating (i.e. conduction, convention or radiation with infrared light) microwave irradiation offers several advantages such as rapid volumetric heating, no overheating at the surface, addressable heating, energy saving and low operating cost [16] …”
Section: Introductionmentioning
confidence: 99%
“…In fact, microwave radiation offers several advantages such as rapid volumetric heating, no overheating at the surface, addressable heating, energy savings, higher yields and lower operating costs and involves much shorter preparation times (Zhou et al, 2003). It has been reported that microwave energy can influence the crystalline status of a drug and that the duration of exposure plays an important role in converting the drug to an amorphous state, thus improving its dissolution rate (Papadimitriou et al, 2008;Tekade et al, 2010;Kumar et al, 2011;Mohanachandran et al, 2010;Moneghini et al, 2008).…”
Section: Introductionmentioning
confidence: 99%